DUNN, Christopher. Brutalidade jardim: a Tropicália e o surgimento da contracultura brasileira. Trad.: Cristina Yamagami. São Paulo: Unesp, 2009 - Kaminski, Leon Frederico (Politeia - História e Sociedade, 2014)
Resumo